1999
DOI: 10.1182/blood.v93.11.3601
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptosis Inhibitor Gene API2 and a Novel 18q Gene,MLT, Are Recurrently Rearranged in the t(11;18)(q21;q21) Associated With Mucosa-Associated Lymphoid Tissue Lymphomas

Abstract: Marginal zone cell lymphomas of the mucosa-associated lymphoid tissue (MALT) are the most common subtype of lymphoma arising at extranodal sites. The t(11;18)(q21;q21) appears to be the key genetic lesion and is found in approximately 50% of cytogenetically abnormal low-grade MALT lymphomas. We show that the API2 gene, encoding an inhibitor of apoptosis also known as c-IAP2, HIAP1, andMIHC, and a novel gene on 18q21 characterized by several Ig-like C2-type domains, named MLT, are recurrently rearranged in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
159
0
8

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 648 publications
(176 citation statements)
references
References 34 publications
9
159
0
8
Order By: Relevance
“…In addition to the detection of t(11;18)(q21;q21), FISH can be used to detect additional aberrations in the breakpoint regions involved (Baens et al, 2000b;Dierlamm et al, 2000) or other translocations involving 11q21 and 18q21 and other partner chromosomes (Streubel et al, 2003). Dierlamm et al (1999Dierlamm et al ( , 2000 showed a cryptic deletion of chromosome 11 sequences distal to the breakpoint in one case. We did not detect this deletion in eight t(11;18)(q21;q21)-positive cases, using the same API2-specific PAC probe.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the detection of t(11;18)(q21;q21), FISH can be used to detect additional aberrations in the breakpoint regions involved (Baens et al, 2000b;Dierlamm et al, 2000) or other translocations involving 11q21 and 18q21 and other partner chromosomes (Streubel et al, 2003). Dierlamm et al (1999Dierlamm et al ( , 2000 showed a cryptic deletion of chromosome 11 sequences distal to the breakpoint in one case. We did not detect this deletion in eight t(11;18)(q21;q21)-positive cases, using the same API2-specific PAC probe.…”
Section: Discussionmentioning
confidence: 99%
“…The most characteristic structural chromosomal rearrangement in MZL has been the t(11;18)(q21;q21) reported in up to 50% of extranodal MZL (Auer et al, 1997;Ott et al, 1997). It involves the apoptosis inhibitor-2 (API2) gene in 11q21 and the mucosa-associated lymphoid tissue (MALT) lymphoma-associated translocation gene (MALT1) in 18q21 (Dierlamm et al, 1999). We found this translocation in only one extranodal MZL, where it was the sole abnormality (case 4).…”
Section: Discussionmentioning
confidence: 81%
“…27) API2-MALT1 chimeric products were identified as a result of the analysis of t(11;18)(q21;q21). [28][29][30] MALT1 is a novel protein with unknown function. 28,29) BCL10 was isolated from the chromosome translocation junction region at 1p22 that is activated by juxtaposition of the IgH gene in t(1;14)(p22;q34).…”
Section: Malt Lymphomamentioning
confidence: 99%
“…[28][29][30] MALT1 is a novel protein with unknown function. 28,29) BCL10 was isolated from the chromosome translocation junction region at 1p22 that is activated by juxtaposition of the IgH gene in t(1;14)(p22;q34). 22) It was recently found that MALT1 and BCL10 play an important role in signal transduction of cellsurface antigen receptors on B and T lymphocytes.…”
Section: Malt Lymphomamentioning
confidence: 99%
See 1 more Smart Citation